Reconstruction of Islamic Education Curriculum in The Disruption Era - Desfa Yusmaliana; Hendro Widodo (IJISH (International Journal of Islamic Studies and Humanities), 2019)
This study aims to reconstruct the curriculum of Islamic education in facing the disruption era. So far, the Islamic education curriculum has not been prepared to face the disruption era which is full of changes. The formal Islamic education curriculum is too crowded with rigid learning administration activities, not inspiration and enlightenment that can build awareness, especially character. This research is a literature review with a qualitative descriptive approach. The results showed that the reconstruction of the Islamic education curriculum in the disruption era is an Islamic education curriculum that developed the character of the millennial generation with digital technology-based learning tools so that learning became more inspiring, enlightening, and building up the Islamic values